Feasibility of Recovery Assessment Scale – Domains and Stages (RAS-DS) for everyday mental health practice - Ramesh, Shivani; Scanlan, Justin Newton; Honey, Anne; Hancock, Nicola (Frontiers in Psychiatry, 2024)
Introduction: Routine use of self-rated measures of mental health recovery can support recoveryoriented practice. However, to be widely adopted, outcome measures must be feasible. This study examined the feasibility of Recovery Assessment Scale -Domains and Stages (RAS-DS) from the perspectives of mental health workers.Method: Mental health workers who had previously sought permission to use RAS-DS (n=58) completed an online survey that explored three aspects of feasibility: practicality, acceptability and applicability.Results: The highest-rated feasibility items related to applicability, or usefulness in practice, with over 90% of participants reporting that RAS-DS helps "promote discussion" and covers areas that are "meaningful to consumers". Acceptability items indicated that the purpose of RAS-DS is clear but length was an issue for some participants. At a practical level, RAS-DS was seen as easy to access but training was seen by many as necessary to ensure optimal use. Conclusions: Results suggest potential usefulness of RAS-DS as a routine outcome measure and identify aspects that can be addressed to further enhance feasibility including provision of training materials and opportunities, wide-reaching promotion of its use as a collaborative tool, and further investigation of issues around instrument length.